Pengaruh Financial Literacy , Financialbehavior, dan Overconfidence Terhadap Keputusan Investasi pada Generasi Z Fakultas Ekonomi Universitas Islam Kadiri - Hanifah Laila Kusumawati; Ahmad Idris; Trisnia Widuri (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
This study aims to determine the effect of financial literacy, financial behavior and overconfidence on investment decisions in generation Z of the Faculty of Economics, Islamic University of Kadiri. This type of research is quantitative research. The data for this study were obtained through questionnaires and literature studies. The analysis techniques used were Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, t-test, F-test and Determination Coefficient Test. The results of the t-test of the financial literacy, financial behavior, overconfidence variables on investment decisions with sig <0.05. The results of the F test can be concluded that financial literacy, financial behavior, overconfidence on investment decisions have a simultaneous and significant effect with sig. <0.05.